The Efficacy of Active Fistulation in Duckett Procedure for Proximal Hypospadias in Children - Ji, Linghua; Yang, Ze; JI, Tianyi; Yang, Yang; Yin, Qiyou; Xian, Hua; Ge , Wenliang (Urology Journal, 2024)
Purpose: To explore the efficacy of active fistulation in the treatment of proximal hypospadias in children by comparing one-stage and two-stage Duckett procedure. Materials and Methods: A total of sixty-seven children who were diagnosed with proximal hypospadias and underwent Duckett operation at our hospital between January 2013 and January 2021 were selected for this study. These subjects were divided into two groups: the research group (n = 36), using two-stage Duckett procedure with active fistulation, and the control group (n = 31), using one-stage Duckett procedure. The incidence of postoperative complications and the score of pediatric penile perception Scale were compared between the two groups. Results: The research group exhibits a significantly lower incidence rate of urethral fistula (8.3% Vs 16.1%) and urethral stricture (5.6% Vs 12.9%) in comparison to the control group (P < 0.01). Furthermore, the analysis of Pediatric Penile Perception Scale scores indicates that the research group achieves significantly higher scores in terms of urethral shape, penile skin shape, and overall appearance than the control group (P < 0.05). Conclusion: In the treatment of proximal hypospadias in children, active fistulation within the two-stage Duckett procedure significantly reduces the rate of stage 1 postoperative complications and improves parental satisfaction. Active fistulation may offer a more promising option for the treatment of proximal hypospadias in children.